Gambaran Penerapan Kompres Air Hangat Terhadap Penurunan Suhu Tubuh Pada Pasien Demam Tifoid Di Ruang Nuri Rumah Sakit Dr. H. Abdul Moeloek Provinsi Lampung - Pujiarto Pujiarto (Jurnal Kesehatan Panca Bhakti Lampung, 2018)
Typhoid fever is a systemic infectious disease caused by Salmonella typhi (s. typhi) which are found extensively in various developing countries including Indonesia. The symptoms of this disease is very varied, depending on the level of stadiumnya. These diseases include infectious diseases listed in Act No. 6 in 1962 about the outbreak. One of the symptoms of this disease is prolonged fever. Fever (hipertermi) is a State in which the body temperature is higher than normal, normal body temperature is a 36.5°C-37,5°C. Fever can be dangerous indeed arise in high temperature, fever or high body temperature can be scaled in various ways, one of which is by way of compresses of warm water to lower body temperature. The purpose of this research is to know the influence of the warm water compress against the granting of a decrease in the temperature of the body temperature on typhoid fever patients. The design used in this research is a case study with intervention implementation. With the subject of 2 people who do temperature measurement before and after do compresses of warm water. The results of this research can be the patient's body temperature to decrease patient one from 38,5’C decreased to 37’C and patient two from 38,9’C decreased to 36,9’C. His conclusion application of warm compresses more effectively lowers body temperature for typoid fever.